Customer Participation in Professional Services Operations And Its Impacts On Flexibility and Costs - Juliana Barreto; Ricardo Silveira Martins (BBR: Brazilian Business Review)
This study has its contribution to deepen the understanding about the paradoxical relation between flexibility and costs in the field of operations service strategy and management, approaching the customer participation affects on the professional services. Through a multi-case study with four professional services organizations, using data collection through semi-structured interviews and documentary research, we identified four main sources of variability, namely: customer arrival, the diagnosis of needs, production and implementation and the delivery value analysis. We concluded that the professional services firms prioritize customer participation and this implies to accommodate variability in flexible service operations to meet the most different types of customers without an alignment to the strategic plan for business growth.